ANALISIS PERAN PEMERINTAH DALAM PERCEPATAN INDUSTRIALISASI DI PROVINSI BENGKULU - Mutia Pratiwi; Santoso, Dwi Budi (Journal of Development Economic and Social Studies, 2022)
The degradation in economic growth in Bengkulu Province was in line with a low growth from the industrial sector. The growth of the Bengkulu Province industrial sector has experienced a significant decline every year. This decrease is called the condition of deindustrialization in Bengkulu Province. Therefore, this study aims to see how big the government's role is in increasing investment efficiency and the impact of investment efficiency in accelerating industrial growth in 9 (nine) urban districts in Bengkulu Province from 2016-2019. The study was conducted using the three-stage least square (3SLS) simultaneous method with panel data. The results of the study show that investment efficiency has no effect on the acceleration of industrialization growth in Bengkulu Province. This indicates that industrial growth in Bengkulu Province has not yet reached economies of scale. This study also shows the results that the education index needs to be the main focus to increase efficiency. So that it is expected to be able to pay more attention to the education index in order to reduce investment efficiency in accelerating the growth of industrial governments.